Parent-identified intrinsic and extrinsic factors that influence performance across developmental domains and participation in their communities - Bican, Rachel; Shaffer, Sydney; Kinkade, Jayna; McAdams, Quinn; Hughes, Allyson S. (Frontiers in Pediatrics, 2025)
Children with neurodevelopmental disabilities living in rural and low-resourced regions within the United States, such as Appalachia, face gaps and barriers to accessing healthcare services due to a shortage of providers, specialists, hospitals, and clinics. Without access to specialized medical and rehabilitation services, their performance across developmental domains and participation within their communities is likely suboptimal. The purpose of this study was to identify both intrinsic and extrinsic factors using a mixed-methods approach to better understand factors that may impact performance across developmental domains and participation for children with disabilities living in Appalachia. Parents completed one study visit in which they completed a total of 4 surveys and a semi-structured interview. The surveys included a parent survey (demographic information, medical history for the child, and barriers to receiving healthcare for their child), health literacy screen, the F-Words Life Wheel, and the Pediatric Evaluation of Disability Inventory (PEDI-CAT). The semi-structured interview asked questions in five primary categories: (1) background, (2) understanding of their child's medical diagnosis and management of their disability, (3) insurance coverage, (4) barriers to receiving healthcare, and (5) social support. This cross-sectional study included n = 17 parents of n = 26 children with neurodevelopmental disabilities. Themes from the interviews were coded both inductively and deductively. Most of the children had delays in important developmental domains, indicating a need for rehabilitation services. Participants reported significant difficulty finding specialists due to the distance from their house to the specialist, they experienced long waitlists and delayed diagnoses, they had difficulties finding caregivers for their children, they frequently had multiple children with disabilities, and they experience sleep disruptions due to their child(ren) with neurodevelopmental disabilities. The authors provide clinical research recommendations and policy changes that may be considered to help mitigate barriers to healthcare for children with neurodevelopmental disabilities living in rural and low-resourced regions.